2007
DOI: 10.1021/np060505o
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cancer Chemopreventive in Vitro Activities of Monomeric Xanthone Derivatives from the Marine Algicolous Fungus Monodictys putredinis

Abstract: Investigation of the fungal strain Monodictys putredinis isolated from the inner tissue of a marine green alga led to the isolation of four new monomeric xanthones and a benzophenone. All structures were elucidated by extensive spectroscopic measurements. The relative configuration of compound 1 was determined by X-ray crystal structure analysis, while for 2 and 3 configurations were confirmed by NOE experiments. Absolute configurations for compounds 1-3 were deduced by comparing experimental circular dichrois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 42 publications
5
84
0
Order By: Relevance
“…A NOESY correlation of H-7 with H 3 -13 suggested a cis relationship for the 7,8-diol moiety, implying that its absolute configuration could be assigned using the in situ dimolybdenum CD method developed by Frelek. 24,25 Upon addition of dimolybdenum tetraacteate [Mo 2 (OAc) 4 ] to a solution of 3 in DMSO, a metal complex was generated as an auxiliary chromophore. Since the contribution from the inherent CD resulting from the C-9 and C-12 carbonyls was subtracted to give the induced CD of the complex, the observed sign of the Cotton effect in the induced spectrum originates solely from the chirality of the Vic-diol moiety expressed by the sign of the O-C-C-O torsion angle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A NOESY correlation of H-7 with H 3 -13 suggested a cis relationship for the 7,8-diol moiety, implying that its absolute configuration could be assigned using the in situ dimolybdenum CD method developed by Frelek. 24,25 Upon addition of dimolybdenum tetraacteate [Mo 2 (OAc) 4 ] to a solution of 3 in DMSO, a metal complex was generated as an auxiliary chromophore. Since the contribution from the inherent CD resulting from the C-9 and C-12 carbonyls was subtracted to give the induced CD of the complex, the observed sign of the Cotton effect in the induced spectrum originates solely from the chirality of the Vic-diol moiety expressed by the sign of the O-C-C-O torsion angle.…”
Section: Resultsmentioning
confidence: 99%
“…The absolute configuration of C-8 was assigned via the CD data of the [Rh 2 (OCOCF 3 ) 4 ] complex, 26 with the inherent contribution subtracted. Upon addition of [Rh 2 (OCOCF 3 ) 4 ] to a solution of 5 in CH 2 Cl 2 , a metal complex was generated as an auxiliary chromophore. It has been demonstrated that the sign of the E band (at ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal metabolites with azol rings act as inhibitors of different P450 enzymes including aromatase (Zhang et al 2002). Various other fungal metabolites, such as monomeric xanthones, benzophenone, depsidones and diaryl ethers, also inhibit P450 enzymes (Krick et al 2007;Chomcheon et al 2009;Sureram et al 2012). In this work, isolates NFW3 and NFW9 showed aromatase inhibition of 73.3 and 76.4% with IC 50 values of 12.2 and 10.5 lg/mL, respectively.…”
Section: Discussionmentioning
confidence: 56%
“…Some compounds suppressing superoxide generation and showing antioxidant activity are associated with cancer chemoprevention (Krick et al 2007). To determine the free radical scavenging potential of our samples, the DPPH assay was performed.…”
Section: Discussionmentioning
confidence: 99%